Spatial Positioning of RET and H4 Following Radiation Exposure Leads to Tumor Development - Yuri E. Nikiforov (The Scientific World Journal)
Exposure to ionizing radiation is a well-known risk factor for a number of human cancers, including leukemia, thyroid cancer, soft tissue sarcomas, and many others. Although it has been known for a long time that radiation exposure to the cell results in extensive DNA damage, including double strand DNA breaks, the exact mechanisms of radiation-induced carcinogenesis remain unknown. Recently, a large increase in incidence of thyroid cancer was observed in children exposed to radiation after the Chernobyl nuclear accident [1]. A high prevalence of chromosomal rearrangements involving the RET gene was found among these radiation-induced thyroid tumors [2,3]. As a result of such rearrangement, a portion of the RET gene is fused with another gene, typically with the H4 or ELE1. However, since the DNA targets of ionizing radiation are randomly distributed throughout the cell nucleus, the reason for predilection for the RET rearrangements in thyroid cells was unclear.